2018
DOI: 10.1371/journal.pone.0206874
|View full text |Cite
|
Sign up to set email alerts
|

Does walking protect against decline in cognitive functioning among breast cancer patients undergoing chemotherapy? Results from a small randomised controlled trial

Abstract: BackgroundCancer related cognitive impairments have been subjectively reported and objectively detected in breast cancer patients treated with chemotherapy and are known to have a profound negative impact on productivity, psychosocial well-being and overall quality of life. Moderate levels of walking are known to be of benefit to the psychosocial well-being of those affected by breast cancer and for managing cognitive impairment in healthy adults, children, and the elderly. The purpose of this study is to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(82 citation statements)
references
References 81 publications
0
65
0
2
Order By: Relevance
“…Walking exercise increased the size of the hippocampus and improved memory in the elderly [24]. In addition, walking exercise reduced self-reported cognitive failure and improved subjective cognitive function in breast cancer patients [25]. These findings indicate that the application of nonpharmacologic interventions such as compensatory calendar training and walking-based exercise regimens can improve cognitive function and help maintain daily life functions.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Walking exercise increased the size of the hippocampus and improved memory in the elderly [24]. In addition, walking exercise reduced self-reported cognitive failure and improved subjective cognitive function in breast cancer patients [25]. These findings indicate that the application of nonpharmacologic interventions such as compensatory calendar training and walking-based exercise regimens can improve cognitive function and help maintain daily life functions.…”
Section: Introductionmentioning
confidence: 79%
“…After intervention, memory contentment increased in experimental group 1 and was maintained in experimental group 2, but decreased in the control group. Gokal et al [25] reported that walking exercise improved subjective evaluations of cognitive function in breast cancer patients receiving chemotherapy. This is consistent with the results of this study, and we concluded that walking exercises improve memory satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity has also proven beneficial for CI, which may be at least partially explained by improvements in symptoms of depression that result from increased behavioral activation 45 . Further, there is evidence that even low intensity exercises can benefit cognition 46 . Physicians and their patients would thus benefit from discussions around the incorporation of physical activity into the treatment plan at diagnosis and before beginning treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the National Comprehensive Cancer Network recommends pharmacologic interventions as a last line of therapy for patients with CRCI, 68 highlighting the importance of developing and evaluating nonpharmacological approaches for this condition. Cognitive rehabilitation and/or training, 69‐73 physical activity, 74‐78 yoga, 79‐81 qi gong, 82 and mindfulness techniques 83,84 have demonstrated preliminary benefits for subjective and/or objective cognitive function in cancer populations, but these findings need to be confirmed in larger, rigorously designed trials. The results of the current study have contributed to this growing literature by highlighting 2 other nonpharmacological interventions that warrant further investigation in the development of effective treatments of CRCI.…”
Section: Discussionmentioning
confidence: 99%